The nodal positivity rate in breast pCR patients with initially, clinically node-negative breast cancer after neoadjuvant systemic therapy: A systematic review and meta-analysis - Ma, Le; Chen, Heyan; He, Jianjun; Xie, Peiling; Gao, Pin; Li, Yijun; Zhang, Huimin; Fan, Zhimin (Frontiers in Oncology, 2023)
Background: The axillary lymph node positive (ypN+) rate in patients with clinically node-negative (cN0) breast cancer who have achieved breast pathologic complete response (bpCR) after neoadjuvant systemic therapy (NST) is extremely low, and this population has the potential to be exempt from sentinel lymph node biopsy (SLNB). However, an overview of the ypN+ rate in this population for different breast cancer subtypes is lacking. Objective: To provide the pooled ypN+ rate in cN0 patients who achieved bpCR after NST in different breast cancer subtypes defined by hormone receptor (HR) status and human epidermal growth factor receptor 2 (HER2) status. Methods: A systematic literature search was conducted in Embase and PubMed on July 20, 2022. Two authors independently selected studies that met the inclusion criteria and extracted all data. The pooled ypN+ rates for each subtype were calculated by a random-effects model using the Stata 16.0 metaprop command. Results: The pooled analysis of 9609 cN0 patients who achieved bpCR showed that the ypN+ rate was lowest for the HR+/HER2+ (0%) subtype, followed by HR+/HER2- (5.1%), HR-/HER2+ (0.6%), and HR-/HER2- (0.3%). Additionally, 6571 cT1-T2N0 patients who achieved bpCR had a pooled ypN+ rate of 0.6%, and the ypN+ rates for different subtypes were as follows: HR+/HER2+ (1.7%), HR+/HER2- (2.7%), HR-/HER2+ (0.1%), and HR-/HER2- (0.8%). Conclusions: Our results suggested that cN0 patients who achieve bpCR may be exempt from axillary surgery in the HR+/HER2-, HR+/HER2+, and HR-/HER2- subtypes because of the extremely low probability of residual axillary lymph node disease. However, the safety of omitting axillary surgery needs to be further confirmed by prospective studies.